Shared Next Generation ILSs and Academic Library Consortia: Trends, Opportunities and Challenges - Guoying Liu; Ping Fu (International Journal of Librarianship (IJoL), 2018)
Next generation Integrated Library Systems (ILSs) have been maturing and adopted by more and more academic libraries. Many academic libraries have joined a consortium to collaboratively move towards a shared next generation ILS that sustains a deeper collaboration. Has this been a trend for academic libraries to share the new system in consortia? This article examines the adoption of the leading products in next generation ILSs to reveal the trend. Two case studies are conducted on A) a pioneer consortial adopter and B) a newly formed partnership on shared next generation ILSs, for further investigations on the impact on consortial members, the challenges the new shared system may cause, and the opportunities it brings to academic library consortia and their members.